Ternary combinational logic gate design based on tri-valued memristors - Li, Xiao-Jing; Wang, Xiao-Yuan; Li, Pu; Iu, Herbert H. C.; Cheng, Zhi-Qun (Frontiers in Physics, 2023)
Traditional binary combinational logic circuits are generally obtained by cascading multiple basic logic gate circuits, using more components and complicated wiring. In contrast to the binary logic circuit design in this method, ternary combinational logic circuit implementation is more complicated. In this paper, a ternary circuit design method that does not require cascading basic ternary logic gates is proposed based on a tri-valued memristor, which can directly realize specific logic functions through a series connection of memristors. The ternary encoder, ternary decoder, ternary comparator, and ternary data selector are implemented by this method, and the effectiveness of the circuits is verified by LTspice simulations.